Volatile fingerprinting of potato rots during cold storage - Gutiérrez-Pozo, Maria (Cranfield University, 2018)
Poster presented at the Cranfield Doctoral Network Annual Event 2018. Winner of the best poster presentation. Potato is one of the main food crops in the world after rice, maize and wheat. Half of it is sold as a fresh product for immediate use, while the rest is stored at cold temperatures (4-10oC) for up to 10 months. Storage is a dynamic situation where all environmental factors, mainly temperature (4-10oC) and relative humidity (95-98%), need to be optimised. Otherwise, an optimal environment for fungal and bacterial growth can emerge. Potato storage diseases have a significant impact on the potato market increasing potato spoilage and consequently, the generation of waste.The aim of this work is the identification of potato rots VOCs (Volatile Organic Compounds) biomarkers as a quick, non-destructive and real time detection of potato storage diseases. The work focused on the three main diseases affecting potato tubers in the last year; soft rot (Pectobacterium carotovorum), gangrene (Boeremia foveata) and dry rot (Fusarium solani coeruleum). Potato tubers were inoculated with those pathogens and stored under different temperatures (10-25oC). VOCs were sampled using a pre-concentration method, thermal desorption tubes that were analysed on a Thermal Desorption-Gas Chromatography-Time of flight-Mass Spectrometry equipment. A screening of the results were carried out for the identification of possible biomarkers of each of the pathogens studied.The results will be used for the development of a prototype of an interactive storage system. It will be a low-cost, compact and sensitive multi-species trace gas that monitors emitted gases from fresh agro products under commercial storage conditions.
Keywords: potato; fungal diseases; bacterial disease; CranfieldDN2018; Food Packaging; Preservation and Safety